PENGARUH PRAKTIK TATA KELOLA PERUSAHAAN YANG BAIK TERHADAP PENGUNGKAPAN LINGKUNGAN PERUSAHAAN - Pradesta Ariningtika; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effect of the practice of good corporate governance on corporate environmental disclosure. The practice of good corporate governance is proxied by the proportion of the board of commissioners, the number of meetings the board, audit committee size and the number of audit committee meetings. This study also includes profitability, company size and leverage as control variables. The population of this research is the mining industry companies are listed on the Indonesia Stock Exchange (IDX) 2010-2011. Total observations is 38 mining companies. Sampling technique in this study is purposive sampling method. The data analysis techniques use multiple linear regression method. The results showed that the number of meetings of the board of commissioners and the size of the audit committee significantly influence corporate environmental disclosure. Meanwhile, the proportion of independent commissioners, the number of audit committee meetings, profitability, company size and leverage did not significantly influence towards corporate environmental disclosure